2022
DOI: 10.3390/molecules27123675
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Immunoassay with a Copper Polymer as the Signal Label for Catalytic Oxidation of O-Phenylenediamine

Abstract: This work suggested that Cu2+ ion coordinated by the peptide with a histidine (His or H) residue in the first position from the free N-terminal reveals oxidase-mimicking activity. A biotinylated polymer was prepared by modifying His residues on the side chain amino groups of lysine residues (denoted as KH) to chelate multiple Cu2+ ions. The resulting biotin-poly-(KH-Cu)20 polymer with multiple catalytic sites was employed as the signal label for immunoassay. Prostate specific antigen (PSA) was determined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The electrochemical and fluorescent methods show a detection limit of 0.40 and 1.00 pg/mL, respectively. Meanwhile, it was found that the Cu 2+ complexes performed with the His1-containing peptides reveal high activity for the catalytic oxidation of OPD to produce fluorescent 2,3-diaminophenazine (OPDox) and maintained excellent selectivity for PSA detection even in the presence of high concentration of interfering proteins [ 88 ]. Based on the difference in the redox potential and current of Cu 2+ before and after being coordinated by the His1- or His3-containing peptide, Feng et al proposed a general, label-free, and homogeneous electrochemical biosensor for the detection of protease activity [ 89 ].…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…The electrochemical and fluorescent methods show a detection limit of 0.40 and 1.00 pg/mL, respectively. Meanwhile, it was found that the Cu 2+ complexes performed with the His1-containing peptides reveal high activity for the catalytic oxidation of OPD to produce fluorescent 2,3-diaminophenazine (OPDox) and maintained excellent selectivity for PSA detection even in the presence of high concentration of interfering proteins [ 88 ]. Based on the difference in the redox potential and current of Cu 2+ before and after being coordinated by the His1- or His3-containing peptide, Feng et al proposed a general, label-free, and homogeneous electrochemical biosensor for the detection of protease activity [ 89 ].…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%